Brock biology of microorganisms - Madigan, Michael T. 1949-; Bender, Kelly S. 1977-; Buckley, Daniel H. (Daniel Hezekiah); Sattley, W. Matthew 1975-; Stahl, David Allan 1949- (Pearson Education Limited, 2022)
'Brock Biology of Microorganisms' sets the standard for impeccable scholarship, accuracy, and strong coverage of ecology, evolution, and metabolism. The sixteenth edition seamlessly integrates the most current science, paying particular attention to molecular biology and the genomic revolution. It introduces a flexible, more streamlined organisation with a consistent level of detail and comprehensive art program. It helps students quickly master concepts, both in and outside the classroom, through personalised learning, engaging activities to improve problem solving skills. "For three generations, 'Brock Biology of Microorganisms' has been praised for its accuracy, consistency, and authority in exploring the principles of microbiology in a visually appealing and connected manner. The sixteenth edition continues to weave genomics (and the various "omics" it has spawned) into every chapter, with concrete examples of how these powerful tools have allowed microbiologists to probe deeper and farther into the microbial world than ever before, thus presenting the most recent picture of the science of microbiology. Key features : all 34 'MicroiologyNow' chapter-opening vignettes are new, these introduce each chapter's theme through a recent discovery in microbiology and show how the chapter's content connects with real-world problems ; three 'Explore the Microbial World' boxes address new topics such as the marine methane paradox and endosymbiosis, they provide fascinating stories that underline how important concepts have evolved from microbial research ; new Key Concept statements at the start of every major topic give students a big-picture view of the content to come ; new section on immunotherapy discusses exciting advancements in the use of genetic engineering and molecular immunology to treat cancer ; new section on the human virome describes how metagenomics aids the discovery and isolation of interesting new viruses ; updated chapter on clinical microbiology and immunology has been reorganized into two separate chapters, "Immune Disorders and Antimicrobial Therapy" and "Diagnosing Infectious Diseases", to discuss the topics in greater detail."--From back cover.